Strengthening the institutional support for single mothers in Sabah: Opportunities and challenges - Salmah Topimin; Lim, Beatrice Fui Yee; Noor Fzlinda Fabeil; Haslinda Hasan (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
Single mothers are perceived as one of society's most vulnerable social groups. Faced with both financial and non-financial challenges, achieving the well-being of their family is never easy. Therefore, it is believed that an inclusive support mechanism for single mothers can help them to build a better life, thus improving their well-being. This paper explores the extent to which the current support mechanisms for single mothers are in accordance with their needs and expectations. This paper is prepared based on a qualitative study that was conducted on a group of single mothers in Sabah. However, this paper only presents partial findings from this study. Views and opinions gathered from the interviews conducted with the single mothers are presented as a proposed framework in strengthening the implementation of support mechanisms for single mothers. The views of the single mothers indicate the needs for supports that reflect on the different stages of their motherhood lives. This finding suggests the significance to acknowledge single mothers as a heterogeneous group and this understanding can help to ensure the effectiveness of support mechanisms for them.